Do Uniparental Sanderlings Calidris alba Increase Egg Heat Input to Compensate for Low Nest Attentiveness? - Reneerkens, Jeroen (Public Library of Science, 2011)
Birds breeding in cold environments regularly have to interrupt incubation to forage, causing a trade-off between two mutually exclusive behaviours. Earlier studies showed that uniparental Arctic sandpipers overall spend less time incubating their eggs than biparental species, but interspecific differences in size and ecology were potential confounding factors. This study reports on a within-species comparison of breeding schedules and metal egg temperatures in uni- and biparental sanderlings (Calidris alba) in Northeast Greenland in relation to ambient temperature. We recorded incubation schedules with nest temperature loggers in 34 sanderling clutches (13 uniparentals, 21 biparentals). The temperature of a metal egg placed within the clutch of 17 incubating birds (6 uniparentals, 9 biparentals) was measured as an indicator of the heat put into eggs. Recess frequency, recess duration and total recess time were higher in uniparentals than in biparentals and positively correlated with ambient temperatures in uniparentals only. Uniparental sanderlings maintained significantly higher metal egg temperatures during incubation than biparentals (1.4°C difference on average). Our results suggest that uniparental sanderlings compensate for the lower nest attendance, which may prolong the duration of the incubation period and negatively affect the condition of the hatchlings, by maintaining a higher heat flux into the eggs.